QUALITY OF CARE AND TREATMENT ON EMERGENT THREATS FOR MATERNAL AND NEWBORN - Iwamizu, Yuko; Dewi, Bella Rossana; Lisnawati, Naintina; Sriatmi, Ayun (Jurnal Manajemen Kesehatan Indonesia, 2024)
Pregnant women and newborns are particularly vulnerable during public health emergencies in Indonesia, where there is a lack of specific guidance to support these groups when emergent threats (ET) arise. Health workers, crucial in delivering maternal and newborn health (MNH) services, often fail to anticipate and address the needs of these vulnerable populations adequately.A literature review analyzing 24 articles from PubMed, Dimension, and Web of Science published between 2016 and 2024 focused on emerging infectious diseases, maternal and newborn health, quality of care, referral systems, and small vulnerable newborns. The review identified substantial gaps in the skills and competencies needed to provide high-quality MNH services globally and in Indonesia. Key issues include non-compliance with existing guidelines, inefficient referral coordination, insufficient monitoring of sick mothers, and a lack of preparedness for emergent threats, all contributing to suboptimal MNH outcomes.These gaps could be addressed by adopting improved training and referral systems, as proposed in the new SVN conceptual framework. Essential actions to enhance MNH outcomes include improving guideline compliance, enhancing referral systems, and ensuring comprehensive training for healthcare providers. Developing an integrated tool tailored to Indonesia's needs that includes SVN, sick mothers, infrastructure, referral systems, and infectious disease management is vital. Implementing these strategies can significantly reduce adverse outcomes and enhance care quality for women and newborns during public health crises.